Investigating Membrane‐Mediated Antimicrobial Peptide Interactions with Synchrotron Radiation Far‐Infrared Spectroscopy. Issue 4 (14th January 2022) - Hornemann, Andrea; Eichert, Diane M.; Hoehl, Arne; Tiersch, Brigitte; Ulm, Gerhard; Ryadnov, Maxim G.; Beckhoff, Burkhard
Abstract: Synchrotron radiation‐based Fourier transform infrared spectroscopy enables access to vibrational information from mid over far infrared to even terahertz domains. This information may prove critical for the elucidation of fundamental bio‐molecular phenomena including folding‐mediated innate host defence mechanisms. Antimicrobial peptides (AMPs) represent one of such phenomena. These are major effector molecules of the innate immune system, which favour attack on microbial membranes. AMPs recognise and bind to the membranes whereupon they assemble into pores or channels destabilising the membranes leading to cell death. However, specific molecular interactions responsible for antimicrobial activities have yet to be fully understood. Herein we probe such interactions by assessing molecular specific variations in the near‐THz 400–40 cm −1 range for defined helical AMP templates in reconstituted phospholipid membranes. In particular, we show that a temperature‐dependent spectroscopic analysis, supported by 2D correlative tools, provides direct evidence for the membrane‐induced and folding‐mediated activity of AMPs. The far‐FTIR study offers a direct and information‐rich probe of membrane‐related antimicrobial interactions. Abstract : Synchrotron radiation far‐infrared spectroscopy enables studying the mechanistic behaviour of antimicrobial peptides in reconstituted membranes, and monitoring membrane‐mediated antimicrobial interactions. Membrane polarity, antimicrobial peptide membrane‐mediated conformation, and related electrostatic interactions are key aspects leading to membrane destabilisation.